2020
DOI: 10.3340/jkns.2019.0252
|View full text |Cite
|
Sign up to set email alerts
|

The Dose Dependent Effects of Ruxolitinib on the Invasion and Tumorigenesis in Gliomas Cells via Inhibition of Interferon Gamma-Depended JAK/STAT Signaling Pathway

Abstract: Objective : Glioblastoma multiforme (GBM) is the most aggressive for of brain tumor and treatment often fails due to the invasion of tumor cells into neighboring healthy brain tissues. Activation of the Janus kinase-signal transducer and activator of transcription (JAK/STAT) signaling pathway is essential for normal cellular function including angiogenesis, and has been proposed to have a pivotal role in glioma invasion. This study aimed to determine the dose-dependent effects of ruxolitinib, an inhibitor of J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 31 publications
0
15
0
1
Order By: Relevance
“…In the case of the high CDI group, ruxolitinib was uncovered as one of the candidate drugs. Ruxolitinib was recently found to prevent glioblastoma invasion and tumorigenesis by inhibiting the IFN-induced JAK/STAT signaling pathway [ 94 , 95 ]. Besides, it has also been proposed for use in patients with chronic neutrophilic leukemia for its safety and efficacy in inhibiting JAK1/2 [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the high CDI group, ruxolitinib was uncovered as one of the candidate drugs. Ruxolitinib was recently found to prevent glioblastoma invasion and tumorigenesis by inhibiting the IFN-induced JAK/STAT signaling pathway [ 94 , 95 ]. Besides, it has also been proposed for use in patients with chronic neutrophilic leukemia for its safety and efficacy in inhibiting JAK1/2 [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Janus kinase (JAK) family of protein tyrosine kinases includes JAK1, JAK2, JAK3, and non-receptor tyrosine kinase 2 (TYK2). 65 JAKs play a key role in intracellular signaling pathways for various cytokines and growth factors essential for hematopoiesis, such as interleukins, erythropoietin, and thrombopoietin. 66 JAKs have multiple functions: JAK1 and JAK3 promote lymphocyte differentiation, survival, and function, while JAK2 promotes signaling of erythropoietin and thrombopoietin.…”
Section: Drugs To Treat Lymphatic Organsmentioning
confidence: 99%
“…147 In 2019, Liu's group noted that axitinib (64) could fit well into the DFG-in conformation, 148 with the indazole part forming two hydrogen bonds with Cys673 and Glu671 in the hinge-binding region, allowing for tighter binding to the VEGFR receptor. Pazopanib (65), also a small molecule inhibitor of multiple protein tyrosine kinases, was approved by the FDA in 2009 for the treatment of advanced renal cell carcinoma and advanced soft tissue sarcoma in patients on prior chemotherapy (Fig. 39).…”
Section: Rsc Medicinal Chemistry Reviewmentioning
confidence: 99%
“…Currently ruxolitinib combined with temozolomide and radiation therapy is investigated for Grade III gliomas and glioblastoma (NCT03514069). Preclinical research showed that treatment with ruxolitinib decreased the U87 malignant glioma cells invasiveness and tumorigenesis [33].…”
Section: Non-receptor Tyrosine Kinasesmentioning
confidence: 99%